Consciousness, attention, and conscious attention - Montemayor, Carlos; Haladjian, Harry Haroutioun, 1973- (The MIT Press, 2015)
"In this book, Carlos Montemayor and Harry Haladjian consider the relationship between consciousness and attention. The cognitive mechanism of attention has often been compared to consciousness, because attention and consciousness appear to share similar qualities. But, Montemayor and Haladjian point out, attention is defined functionally, whereas consciousness is generally defined in terms of its phenomenal character without a clear functional purpose. They offer new insights and proposals about how best to understand and study the relationship between consciousness and attention by examining their functional aspects. The book's ultimate conclusion is that consciousness and attention are largely dissociated. Undertaking a rigorous analysis of current empirical and theoretical work on attention and consciousness, Montemayor and Haladjian propose a spectrum of dissociation--a framework that identifies the levels of dissociation between consciousness and attention--ranging from identity to full dissociation. They argue that conscious attention, the focusing of attention on the contents of awareness, is constituted by overlapping but distinct processes of consciousness and attention. Conscious attention, they claim, evolved after the basic forms of attention, increasing access to the richest kinds of cognitive contents. Montemayor and Haladjian's goal is to help unify the study of consciousness and attention across the disciplines. A focused examination of conscious attention will, they believe, enable theoretical progress that will further our understanding of the human mind"--MIT CogNet.